Social Media - Leaver, Tama (Routledge, 2024)
Almost every Australian over the age of 13 is a social media user. Social and digital media has become part of the everyday landscape of social lives, politics, education and entertainment. Yet Australia’s relationship with the big platforms has become strained in the wake of the Cambridge Analytica scandal in which Facebook showed a lack of care for users’ personal data or the Australian News Media Bargaining Code debates which saw Facebook block news for all Australian users. Following the renewed global interest in government regulation of the major platforms, Australia’s relationships with social media is evolving in more complex directions.